2015
DOI: 10.1073/pnas.1500953112
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium–cysteine coordination in the BK inner pore region and its structural and functional implications

Abstract: To probe structure and gating-associated conformational changes in BK-type potassium (BK) channels, we examined consequences of Cd 2+ coordination with cysteines introduced at two positions in the BK inner pore. At V319C, the equivalent of valine in the conserved Kv proline-valine-proline (PVP) motif, Cd 2+ forms intrasubunit coordination with a native glutamate E321, which would place the side chains of V319C and E321 much closer together than observed in voltage-dependent K + (Kv) channel structures, requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…The gating mechanisms in eukaryotic Ca 2+ - and voltage-gated BK channels have been explored using blockers 19 21 44 45 46 47 48 49 and thiol-modifying probes 20 22 to assess conformational changes within the pore. Taken together, most of these studies are suggestive of a gating mechanism ‘deeper' inside the pore than for K v channels 50 , though a molecular-gating model has yet to be firmly established 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gating mechanisms in eukaryotic Ca 2+ - and voltage-gated BK channels have been explored using blockers 19 21 44 45 46 47 48 49 and thiol-modifying probes 20 22 to assess conformational changes within the pore. Taken together, most of these studies are suggestive of a gating mechanism ‘deeper' inside the pore than for K v channels 50 , though a molecular-gating model has yet to be firmly established 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of voltage-gated channels, numerous functional studies have shown that activation gating involves the opening of an intracellular gate 14 17 18 . Alternatively, several types of ligand-gated channels, including BK channels 19 20 21 22 , have been proposed to employ a different activation gating mechanism that involves changes at the selectivity filter 23 24 25 26 27 28 . However, the studies in support of selectivity filter gating in BK channels are not definitive due to the complexity of BK channel gating (voltage- and Ca 2+ -dependent gating) combined with the use of voltage-dependent blockers, leading to uncertainty in identification of the gate location.…”
mentioning
confidence: 99%
“…Previously, metal‐mediated reactions activating otherwise inert endogenous amino acids had been developed, resulting in the addition of reactions to the protein modification “toolbox” . Sulfur atoms within cysteine residues are capable of binding to a wide range of metal ions, including iron, zinc and cadmium (namely soft metal centres) . Protein immobilisation onto gold plates through cysteine residues for surface plasmon resonance (SPR) is well established .…”
Section: Use Of Metals In Cysteine Modificationmentioning
confidence: 99%
“…As development proceeds, P granules congregate and localize to the posterior size of the embryo, which helps to establish the asymmetric division and subsequent generation of germ cells (Schneider and Bowerman, 2003). Other membrane-less compartments resulting from protein/RNA interactions include nucleolus (Berry et al, 2015), the phase formed at the tail of RNA polymerase II during transcription (Kwon et al, 2013), stress granules (Wippich et al, 2013). …”
Section: Introductionmentioning
confidence: 99%